Dinâmicas de preços: um estudo dos impactos da estiagem do rio Solimões sobre os preços dos alimentos da cesta básica no ano de 2024 e seus efeitos sobre a população de Benjamin Constant-AM - Silva, Eduardo da Silva e (Brasil, 2025)
The ebb and flow of the Solimões River, an annual phenomenon that occurs in the Amazon region, has serious logistical and economic impacts, especially in municipalities such as Benjamin Constant-AM. During this period, the reduction in water levels compromises navigation and makes the transport of goods more expensive, including essential foodstuffs from the basic food basket. This work explores the price dynamics resulting from the drought. The general objective of this study was to understand the impact of the Solimões River's ebb and flow on the prices of basic foodstuffs in Benjamin Constant-AM. The methodological procedures that guided the research involved a qualitative and descriptive approach. The data was obtained through a documentary survey and field research, which was carried out using a questionnaire with six businessmen and ten consumers. As a result of the research, it was found that all traders and consumers are aware of the impact that the drought of the Solimões River has on the basic food basket, and that the real reason for the rise in prices is the combination of drought and logistical costs, which generates an additional expense. We conclude that this work has fulfilled its objectives by analysing in detail the impacts of the Solimões River drought on the prices of foodstuffs in the basic food basket in Benjamin Constant-AM, highlighting the negative effects on consumers‘ finances and traders’ operations. The research highlighted the importance of the logistical issue generated by the ebb and flow and its impact on product costs. Although the results obtained are significant, we suggest expanding the sample and carrying out future studies with more time and participation, in order to strengthen the findings and contribute to public policies that minimise the effects of this crisis.